GC-MS Analysis and In-silico Molecular Docking study of Skin Fruit Arabica Coffee (Coffea arabica L.) Methanol Extract as Mosquito Repellent: english - Rita Maliza; Husna Fitri; Bramadi Arya (Biota, 2023)
Malaria is an endemic disease that is still a problem globally, especially in countries with tropical and subtropical climates. People generally use mosquito repellents from synthetic materials, but they still cause effects and toxicity. Using active compounds from plants is an alternative to developing mosquito repellents. The 30 active compounds from the GC-MS analysis of methanol extract of Arabica coffee skin fruit and we selected the highest percentage compound, namely n-Hexadecanoic acid, Caffeine, Hexadecanoic acid methyl ester, 3-O-Methyl-d-glucose and desulphosinigrin. The highest compounds were carried out by molecular docking with Odorant binding protein 1 (OBP1) as the protein target and N, N-Diethyl-3-methylbenzamide (DEET) as the native ligand. Desulphosinigrin has the highest binding affinity, which is -6.2 Kcal/mol, close to the native ligand DEET. It can be concluded that the active compound desulphosinigrin has the potential as a repellent. This study concludes that active compounds from the methanol extract of Arabica coffee skin have the potential as a repellent.